Strategi Keunggulan Bersaing pada Perguruan Tinggi Swasta di Kota Kupang - Angela Merici Minggu; Eka M. I. Seseli (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2018)
This study aims to describe the competitive advantage strategy conducted by PTS in the City of Kupang by using Porter's five forces model analysis (1980). Using a qualitative approach to obtain descriptions that explain the competitive advantage strategies of private universities, the three private universities which were ranked as the top 3 in Kupang City, Widya Mandira Catholic University, Muhammadiyah Kupang University, and Artha Wacana Christian University were made participants in this study. The three PTSs have the development of resources and strategies that become competitive in order to maintain and even improve their quality and survive. The study found that the three universities placed key priorities in their respective competition, in general there was a strategy to improve the quality of higher education, build networking with other universities or the government, and improve administrative and academic services towards students.